2018
DOI: 10.1126/sciadv.aar5100
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient electrochemical reforming of CH 4 /CO 2 in a solid oxide electrolyser

Abstract: Electrochemical reforming of CH4/CO2 is demonstrated in a solid oxide electrolyser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(78 citation statements)
references
References 36 publications
2
75
0
Order By: Relevance
“…However,i tw as hard to determine whether the Ni 2 + were loaded by doping or ion exchange in theset wo samples. 1 HNMR spectra happened to be able to further clarify the introduction of Ni 2 + in Ni 2 + -CSH-Dop and Ni 2 + -CSH-Iex according to the signals of silanol groups (Si-OH). (Figure 9) In 1 HNMR spectra of ACS and CSH, the chemical shift at 1.29 ppm could be attributedt ot he signal of the terminal Hi n Si-OH.…”
Section: G)mentioning
confidence: 99%
See 1 more Smart Citation
“…However,i tw as hard to determine whether the Ni 2 + were loaded by doping or ion exchange in theset wo samples. 1 HNMR spectra happened to be able to further clarify the introduction of Ni 2 + in Ni 2 + -CSH-Dop and Ni 2 + -CSH-Iex according to the signals of silanol groups (Si-OH). (Figure 9) In 1 HNMR spectra of ACS and CSH, the chemical shift at 1.29 ppm could be attributedt ot he signal of the terminal Hi n Si-OH.…”
Section: G)mentioning
confidence: 99%
“…The dry reforming of CH 4 (DRM) with CO 2 hasb een considered as an effective method to convert CH 4 into syngas. [1] This reaction pathway is not only beneficial for the reduction of greenhouse gases such as CH 4 and CO 2 ,b ut also capable of producing syngasw ith H 2 /CO ratio desired by the downstream industrial process. [2] Although the great value of DRM reaction in environmentp rotection and industrial applications has been recognized by many people, the development of metal catalysts for this reaction still requires more attentionc onsidering the large number of side reactions and the highly endothermic feature in the DRM process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that exsolved particles are more resilient to agglomeration and coking as compared to the deposited analogues due to the partial embedment of exsolved particles on the perovskite surface. A stronger metal‐support interface is created via the anchoring of exsolved particles on the parent perovskite . Thus, exsolution may be regarded as an elegant one‐step method to grow pinned, coking‐resistant, and socketed particles.…”
Section: Introductionmentioning
confidence: 97%
“…A stronger metal-support interface is created via the anchoring of exsolved particles on the parent perovskite. [61,62] Thus, exsolution may be regarded as an elegant one-step method to grow pinned, coking-resistant, and socketed particles.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Recently,e lectrochemical conversion of alkanes based on solid oxide electrolysis cells (SOECs) has been investigated intensively. [7] With alkane fed to the anode,t he amount of oxygen species involved in oxidative dehydrogenation reaction is controlled electrochemically,s ot he coke formation and deep oxidation can be inhibited by adjusting as uitable current. [8] Theh igh oxidative dehydrogenation activity can be achieved by surface decoration of anode materials,which is efficient to tune the electronic structure and density of state (DOS) of the interfacial atoms,and regulate the surface oxygen species and adsorption free energy.…”
mentioning
confidence: 99%